A Ni(OH)2-modified Ti-doped α-Fe2O3 photoanode for improved photoelectrochemical oxidation of urea: the role of Ni(OH)2 as a cocatalyst1. Issue 37 (7th October 2015) - Xu, Dandan; Fu, Zewen; Wang, Dejun; Lin, Yanhong; Sun, Yanjun; Meng, Dedong; feng Xie, Teng
<x xml:space="preserve">Abstract</x> Ni(OH)2, as a hole storage layer, enhances the separation of photogenerated charge carriers, which contributes to enhanced photocurrent.